INHERITANCE OF COTTON AND QUALITY INDICATORS OF TOLA Ғ1 HYBRID VARIETIES - Narkizilova Gulzira; Toshpulatova Gulnoza; Khusanov Navruzbek; Nazarbaev Khursand; Boboev Safyulla; Mirakhmedov Mirvahob (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the evacuation of the results obtained on fiber consumption and inheritance of certain fiber quality indicators on Ғ1duragay plants obtained with the participation of rubella varieties and families. Depending on the parent genotype of origin and the quality of fiber, inheritance is established on stagnant plants under conditions of intermediate, complete dominance and extreme dominance, unique recombinants are distinguished, on the basis of which the continuation of genetic selection studies ensures the achievement of positive results.